SOSIALISASI PEGENALAN MATA UANG ASING PADA WARGADUSUNBABADAN, DESASELOMIRAH,NGABLAK,MAGELANG, JAWA TENGAH - Mellisa Fitri Ardriyani (Asian Journal of Innovation and Entrepreneurship, 2014)
The lack of information about the various types of currency in circulation led tothe need for more education about theforeign currency. Children who began studyingthe countries schools have curiosity about the currency of each country. Furthermore,along with the rise of counterfeiting currency, the child also need to be introduced inaddition to the authenticity of therupiah currency but also the physical form of anothercountry's currency. Counseling to children with physical eyes showed foreign currencyand interspersed with the game so that children can understand the material well. Thediperkenallkan currency is thecurrency of US dollars, Real Saudi Arabia, the Malaysianringgit and the Thai Bath. Introducing the currency primarily foreign currency willcertainly add insight about the state of children in the world and combat fraud by usingforeign currencies. The method used by using the game will make children more activeand understand the material.